Предмет: Математика, автор: rulezz2000

С решением пожалуйста

Приложения:

Ответы

Автор ответа: Miroslava227
1

1)dy = (4x - 3)dx \\ \int\limits \: dy = \int\limits(4x  - 3)dx \\ y =   \frac{4 {x}^{2} }{2}    - 3x + c \\ y = 2{x}^{2}  - 3x + c

y(0) = 0 \\ 0 = 0 + c \\ c = 0 \\

y = 2 {x}^{2}  - 3x

частное решение

2)xdx = dy \\ \int\limits \: dy = \int\limits \: xdx \\ y =  \frac{ {x}^{2} }{2}  + c

общее решение

y(1) = 0

0 =  \frac{1}{2}  + c \\  c =  -  \frac{1}{2}

y =  \frac{ {x}^{2} }{2}  -  \frac{1}{2}  \\ y =  \frac{ {x}^{2} - 1 }{2}

частное решение

3) \frac{dy}{2x}  =  -  \frac{dx}{y}  \\ \int\limits \: ydy =  - \int\limits2xdx \\  \frac{ {y}^{2} }{2}  =  - 2 \times  \frac{ {x}^{2} }{2}  + c \\  {y}^{2}  =  - 2 {x}^{2}  + c

общее решение

y(0) = 2

4 = 0 + c \\ c = 4

 {y}^{2}  =  - 2 {x}^{2}  + 4

частное решение

Похожие вопросы
Предмет: Математика, автор: Lovins